Effect special skills on training need to the agricultural extension agents using Borich need assessment model - Saleh, Jasim Mohammed; Man, Norsida (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
The study was conducted in Iraq that significantly related to the issue. To identify the training needs of the respondents in the areas of agricultural extension. Therefore, this study is important for the following considerations; it will be led by precise training objectives, which play a significant role in avoiding some of the common mistakes. Better targeting will be helpful in improving the effectiveness and efficiency of training (Muhammad, et al. 2012). A questionnaire survey was adopted for a population of 300 professionals using certified sampling techniques. To analyze the training needs of responders “Borich’s Need Assessment” model technique was used this study which focused on special skills, job satisfaction, information and scientific specialization and social demographic factors. The highest training need was found in the treatment of “name of method, with average mean =3.74, the moderate needed training was found in the treatment “use computer and ICT” (mean=3.26), and the lowest was on “management skill” (Mean = 3.15). Furthermore, the results showed that there was a significant relationship between training needs and the province, marital status, location of work, experience (r = 0.51), the number of training courses attended, special skills, job satisfaction and information.